Empirical study of effectiveness of construction waste minimization in Bauchi state (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper critically investigates and analysed the to determine the level of waste minimization practices in Bauchi State, Nigeria. In practice, there has been a tremendous increase in building construction which led to the generation of waste at different stages of construction. The structure of Nigerian construction industry is complex having different types of clients and contractors. This consist of public and private clients, main contractors and sub-contractors, indigenous and foreign companies, low technology firms and sophisticated specialists, builders and civil engineers and a whole range of construction professionals connected within the industry. The growing popularity of Public Private Partnership (PPPs) also means more international construction firms are likely to come into the Nigerian construction industry. The materials and methods was that questionnaire design was undertaken to determine the opinion of contractors on waste minimization practices in the study area. The sample group identified comprises project managers, project engineers, quantity surveyors, site supervisors and the method of distribution and collection of the questionnaire survey is through google by Survey Monkey. The questionnaire was constructed using Likert scale. The respondents were asked to rank on a scale of 1-5 waste minimization strategies on construction sites. The population of this research were construction firms in Bauchi participating on different types of construction projects. In this research, use of census is administered. A total number of 77 construction firms with valid registration in Nigeria. The result of the survey on the level of waste minimization practices in Bauchi construction industry. Reuse on site with the highest mean of 3.86 is in the high category and ranked first. The reuse on site is the most frequent practice on construction site. The second ranked mean is 3.57 also in the High category which represent the proportion of respondents that minimize waste at the source of origin. The finding of the research study shows that the study emphasized the Reuse is the most acceptable way of waste minimization in construction site in the study area. From the findings of this research study, its recommended that the contraction firms should have waste management plan regardless of its size as this will reduce both physical and non-physical waste and increase the profit